Perbedaan pencapaian kompetensi pengetahuan siswa ditinjau dari buku ajar yang digunakan pada materi fluida statis dan dinamis kelas XI SMAN 2 Padang Panjang - Syamina Syamina; Hamdi Hamdi; Dewi Puspa Sari (Universitas Negeri Padang, 2020)
Some of the skills needed in the 21st century include: the ability to think critically, collaboration and leadership, and have high curiosity. These skills must be prepared by all government agencies and the education environment. In the field of education, specifically in high school, one struggle that can be done is to provide learning resources that are relevant to learning models that are also relevant. Like providing edupark physics books as a source of physics learning for high school. Edupark books have advantages compared to textbooks that are available in general. Therefore a study was conducted to find out the differences between students' knowledge between the application of edupark books and textbooks in schools. The learning model applied to both pf grade is discovery learning. This research was conducted in Class XI of SMAN 2 Padang Panjang in the 2019/2020 school year odd semester on fluid material. The research data consisted of the assessment of posestest scores between 2 classes who requested different textbooks. At a significant level of 0.05, there are significant differences in student physics learning outcomes from aspects of knowledge competence. Based on data analysis on knowledge competency through posttest, experimental class 1 has an average value of 82.5 and experimental class 2 is 76.1. Classes that use the physics edupark book MiFan Water Park Padang Panjang have a higher value of knowledge competence than classes that use textbooks used in schools.